Effect of Mobile Application-Based Interventions on Lifestyle and Outcomes of Patients after Obesity Surgery - Asmaa A. A. Saleh; Ahmed E. I. Mansour (Evidence-Based Nursing Research)
Context: The use of the mobile application in the provision of health care services like patient education has the potential to change patients' behaviors and improve patients outcomes.